SOCIAL INTELLIGENCE AS SHAPED BY FACEBOOK USE - Nawal Kadri (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
With the 21st century increasing globalization and advent in technology, social media has become an integral part of the everyday life of many students. Various websites and mobile applications dedicated to social media notably twitter, Facebook and instagram are popular. As a matter of fact, Facebook is the most ubiquitous social networking site in students’ life; it offers an online platform on which users create profiles, interact and exchange content, share pictures and videos, discuss subjects, follow news, publish advertisements for group events, or play different games. This fact compels us to study its effects on their life. How Facebook shapes students’ life has been the focus of educators and researchers in the last decade. For instance, extensive research has recently been conducted on the effects of this social media on students’ well-being and academic achievement. However, little research is found on its effect on social intelligence, a critical aspect of students’ social life. As such, the present study investigated how Facebook use shapes students’ social intelligence. Specifically, we were interested in exploring how students understand and manage emotions and relationships via the virtual world of Facebook. Subjects were ninety-two (92) students from different Algerian universities. Data was collected via an online survey which aimed at exploring students’ use of facebook: intensity, awareness, attitudes and management. Results indicated a significant relation between Facebook use and students’ social intelligence. The findings also reported the benefits the students experience via Fecebook. However, the participants voiced some concerns regarding its effects. As an outcome of the study, a number of implications were developed. Key words: Algerian students, attitudes, Facebook, social intelligence, social media